PENGARUH SISTEM PERPAJAKAN, KEADILAN, DAN TEKNOLOGI PERPAJAKAN PADA PERSEPSI WAJIB PAJAK MENGENAI PENGGELAPAN PAJAK - Paramita, Mirah Pradnya; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2016)
The purpose of this study is to obtain the empirical evidence of the effect of tax system, justice, and technology of taxation on taxpayer perception about tax evasion. This study is located at Kantor Pelayanan Pajak (KPP) Pratama Badung Utara and the population in this study is an individual taxpayer who is registered in KPP Pratama Badung Utara. The respondents in this study were 100 individual taxprayers were determined using purposive sampling method. The data come from the questionnaires that distributed to respondents and than analyzed with multiple linear regression analysis. The result showed that tax system and justice has negative influence on taxprayers perception about tax evasion. Meanwhile, technology of taxation does’nt has negative influence on taxprayers perception about tax evasion.
Keywords: system, justice, technology, perception